2015
DOI: 10.1182/blood-2015-03-632901
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived VWF is not essential for normal thrombosis and hemostasis but fosters ischemic stroke injury in mice

Abstract: Key Points Platelet-derived VWF alone mediates full ischemic stroke injury in mice via a GPIb-dependent mechanism. Platelet-derived VWF does not significantly contribute to normal thrombosis and hemostasis in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 32 publications
2
57
0
Order By: Relevance
“…11 VWF is synthesized by ECs and megakaryocytes and is stored as ultra large VWF multimers or high molecular weight multimers in the endothelial Weibel-Palade bodies or the platelet α-granules, respectively. 12 Plasma VWF was thought to be derived from the secretion of ECs and platelets and could be enhanced by secretagogues. 12 Although numerous studies have revealed the roles of VWF on hemostasis and coagulation, the differences between the endothelial VWF and the platelet VWF in thrombotic and thrombosis-related diseases are unclear.…”
Section: Von Willebrand Factormentioning
confidence: 99%
See 1 more Smart Citation
“…11 VWF is synthesized by ECs and megakaryocytes and is stored as ultra large VWF multimers or high molecular weight multimers in the endothelial Weibel-Palade bodies or the platelet α-granules, respectively. 12 Plasma VWF was thought to be derived from the secretion of ECs and platelets and could be enhanced by secretagogues. 12 Although numerous studies have revealed the roles of VWF on hemostasis and coagulation, the differences between the endothelial VWF and the platelet VWF in thrombotic and thrombosis-related diseases are unclear.…”
Section: Von Willebrand Factormentioning
confidence: 99%
“…12 Plasma VWF was thought to be derived from the secretion of ECs and platelets and could be enhanced by secretagogues. 12 Although numerous studies have revealed the roles of VWF on hemostasis and coagulation, the differences between the endothelial VWF and the platelet VWF in thrombotic and thrombosis-related diseases are unclear. Dhanesha et al 13 examined the roles of endothelial and platelet VWF in thrombosis in vivo.…”
Section: Von Willebrand Factormentioning
confidence: 99%
“…25 Of note, this study did not quantify the overall local levels of VWF in the infarcted and surrounding region following stroke. Similar to the Verhenne et al study, we found that chimeric Plt-VWF mice exhibited significantly bigger infarcts compared to VWF-KO mice.…”
Section: Discussionmentioning
confidence: 94%
“…1 They created mice with either endothelial VWF or platelet-derived VWF and examined each phenotype for bleeding and thrombosis. Their intriguing findings were that mice lacking platelet-derived VWF, but with adequate endothelial VWF stores, demonstrated normal hemostasis in a tail bleeding model and normal carotid artery thrombosis.…”
mentioning
confidence: 99%
“…Verhenne et al use an anti-GPIba antibody in their stroke model and show a corresponding reduction in the effect of platelet-derived VWF, as would be expected if GPIb is the major driver in this interaction. 1 Platelets themselves have been implicated in stroke, with aspirin playing a key role in treatment and prevention. 6 The paradigm in which antiplatelet agents are used, however, has generally been that of preventing platelet aggregation rather than preventing release of prothrombotic VWF.…”
mentioning
confidence: 99%